The legal review of parking liability for vehicle loss according to the consumer protection law - Fadliyah, Ulfa; Asnawi, Asnawi; Faturohman, Faturohman (Journal of Law Science, 2025)
The loss of motor vehicles in paid parking areas frequently occurs without clear accountability from parking operators. Many operators include liability exemption clauses on parking tickets, such as "loss is not the responsibility of the operator," which contradicts Law Number 8 of 1999 concerning Consumer Protection (UUPK). This study aims to examine the legal liability of parking operators for lost vehicles and to evaluate the effectiveness of the Consumer Dispute Resolution Agency (BPSK) in resolving consumer disputes. A normative juridical approach was employed, involving analysis of legislation, legal doctrines, and case studies. Data were collected through literature reviews, field observations, interviews, and documentation. The findings indicate that parking operators bear strict liability for vehicles under their care but frequently evade responsibility through invalid standard clauses. A case in Serang City revealed that a consumer who lost their vehicle received no compensation, despite presenting a valid parking ticket. Although the BPSK offers a non-litigation mechanism for dispute resolution, its effectiveness is limited by low participation from businesses and restricted authority. Strengthening regulations, enhancing the role of BPSK, and increasing consumer awareness are essential steps toward ensuring fair and effective legal protection.